2009
DOI: 10.1007/s11104-009-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nutrient losses during manure storage under traditional and improved practices in smallholder crop-livestock systems—evidence from Kenya

Abstract: In the absence of mineral fertiliser, animal manure may be the only nutrient resource available to smallholder farmers in Africa, and manure is often the main input of C to the soil when crop residues are removed from the fields. Assessments of C and nutrient balances and cycling within agroecosystems or of greenhouse gas emissions often assume average C and nutrient mass fractions in manure, disregarding the impact that manure storage may have on C and nutrient losses from the system. To quantify such losses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 23 publications
2
38
0
2
Order By: Relevance
“…To increase nutrient conservation, recommendations are to compost under roofs and on floors (Rufino and Rowe, 2006), and to limit storage time (Tittonell et al, 2010). Farmers aim to keep animals longer in confinement by improving forage availability (Landais and Lhoste, 1993).…”
Section: Manure Management Practices -A Global Viewmentioning
confidence: 99%
“…To increase nutrient conservation, recommendations are to compost under roofs and on floors (Rufino and Rowe, 2006), and to limit storage time (Tittonell et al, 2010). Farmers aim to keep animals longer in confinement by improving forage availability (Landais and Lhoste, 1993).…”
Section: Manure Management Practices -A Global Viewmentioning
confidence: 99%
“…If farmers do apply this manure onto the land following storage, the effectiveness of this BMP will have been overestimated here. Previous research [ Tittonell et al ., ; Gooday and Anthony , ] indicates a difference of about 4% in P leakage rates between different manure storage strategies (SI 1). Livestock numbers per subcatchment were calculated using 2011 livestock densities [ Statistics Canada , ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found C losses of 14 to 50% from slurry stores (Amon et al, 2007;VanderZaag et al, 2010aVanderZaag et al, , 2010b) and 35 to 70% from manure heaps (Chadwick, 2005;Petersen and Sorensen, 2008;Tittonell et al, 2010). The CH 4 -C losses from manure heaps can range from 0.4% to 10% of total C (Chadwick, 2005;Webb et al, 2012) but can represent as much as 60 to 70% of total C in raw slurry stores under warm storage conditions (Moset et al, 2012).…”
Section: Nutrient Losses During Winter and Summer Storage Of Separatementioning
confidence: 95%